PERAN GURU DAN BUDAYA SEKOLAH DALAM PEMBENTUKAN KARAKTER SISWA - Robbi Shiddiq (QATHRUNÂ, 2020)
The education taught in Islam is an education that is based on faith and Taqwa. Student's personality will be created and colored by through a process of socialization in his life that takes place in the form of school culture, and interaction with his teachers. The purpose in this study is: (1) To describe the role of teacher in character building of student at mts mathla'ul anwar sukamaju? (2) To describe the development program can form a cultural character in MTs Mathla'ul Anwar Sukamaju? (3) To analyse the school's activities Program affect the formation of student characters in MTs Mathla'ul Anwar Sukamaju? dan (4) To analyse the effective program to form the character of students in MTs Mathla'ul Anwar Sukamaju. The research approach used in this study is a qualitative approach that aims to find out objectively the role of teacher and school culture in character building of student at mts mathla'ul anwar. Data collection techniques used were questionnaire, interview, observation and documentation. The results of his research are: The role of MTs Mathla'ul Anwar Sukamaju's teacher greatly shapes the character of a good student that is able to carry out their duties well by becoming an educator, instructor and at the same time a supervisor. School culture influences the formation of the character of their students where the environment holds the moral of students, the character education program policy at MTs Mathla'ul Anwar has carried out a character education planning by preparing a strategic plan that contains the vision and mission as well as the objectives. and the impact of the successful management of character education was felt by MTs Mathla'ul Anwar Sukamaju increasing the confidence of parents sending their children to this school. Secondly, the growing number of graduates that are acceptable in the Community environment.